Bio-Based Wood Adhesives: Current Advances in Polymer Architecture and Structure–Property–Sustainability Integration - Dangwilailux, Panya; Rachsiriwatcharabul, Natworapol; Lakachaiworakun, Putipong; Eakvanich, Visit; Wattana, Wassachol; Kalasee, Wachara (My University, 2026)
The development of bio-based adhesives has emerged as a viable strategy to reduce fossil-derived resin consumption in wood and wood-based panel applications. This review provides a polymer-focused assessment of adhesive systems derived from proteins, carbohydrates, lignin, and tannins, emphasizing molecular architecture, crosslinking chemistry, interfacial interactions, and structure–property relationships. Adhesive performance is primarily dictated by functional group density, crosslinking efficiency, and network topology. Protein-based adhesives rely on hydrogen bonding and covalent crosslinking with lignocellulosic substrates but require structural modification to improve hydrothermal stability. Carbohydrate-based systems, including starch and cellulose derivatives, offer reactive hydroxyl functionalities that enable oxidation, esterification, and etherification pathways for enhanced network formation. Lignin and tannins, characterized by phenolic and aromatic structures, facilitate condensation reactions and enable partial substitution of phenol in thermosetting resins, supporting low-formaldehyde or formaldehyde-free formulations. Hybrid polymer networks, particularly protein–carbohydrate and lignin-modified systems, demonstrate improved crosslink density, reduced hydrophilicity, and enhanced mechanical performance. Life cycle analyses indicate that increasing biogenic carbon content and minimizing fossil-based cross-linkers can lower global warming potential (GWP) and volatile organic compound (VOC) emissions. Overall, a structure–property–sustainability framework is proposed to guide molecular design and performance optimization of next-generation bio-based wood adhesives.
Keywords: bio-based wood adhesives; crosslinking chemistry; global warming potential; lignin and tannins; wood-based panel